Nilai Kearifan Lokal pada Cerpen Silariang dalam Antologi Cerpen Gadis Pakarena Karya Khrisna Pabichara - Arifa Ainun Rondiyah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
Literature is a form of work in which it combines elements of imagination and real life, both oral and written literature. Literary works contain various aspects, one of which is the cultural aspect which has a very broad scope. Culture itself exists naturally and develops which is done routinely and repeatedly. The value of local wisdom is part of the culture that is the specialty of a literary work, whether it is poetry, novels or short stories. One of the short stories containing the value of local wisdom is in the short story Salirang in the short story anthology book Gadis Pakarena by Khrisna Pabichara. A short story that tells about the value of local wisdom of the Bugis-Makassar community. This study uses a qualitative method. Qualitative methods utilize interpretive methods in presenting data in a descriptive form. The approach used in this research is literary anthropology. The data in this study are in the form of text quotes with the data source being the short story Salariang in the short story anthology book Gadis Pakarena by Khrisna Pabichara. Natural data presented in the form of facts and phenomena that include values, local wisdom. The technique used during data collection is to record documents or archives, so this study uses document analysis with the snippet technique. First, caste in Bugis Makassar society has social status which regulates marriage. Both silariang are violations of customary rules in the form of elopement caused by various things. The three series and pacce for Bugis Makassar are something that is more important than life. Siri which means self-respect while pacce means shame that will never go away Keywords: literature, culture, local wisdom